Breeding Biology of Passer domesticus with Reference to its Conservation in Kashmir, India - Altaf, Sabia; Lateef, Mohamamad; Ahmad, Fayaz (Indian Forester, 2024)
There are many reports on declining population of house sparrow throughout world. The spaces, holes and cavities under roofs are used by the bird for nesting purpose. The expansion of urban areas at the cost of denudation of vegetation and increase in built up areas, concrete cemented buildings without any cavities and crevices has also affected the reproduction and survival of house sparrow. The change in living style and replacement of conventional houses by modern style concrete houses without any space or crevice has left the bird homeless. The present study was carried out to check various aspects of breeding to know if they are facing problems in breeding. The breeding season of the bird extended from March to August during which 2 to 3 broods were raised. The average clutch size was 4.25 while average incubation period was 12 days. Both sexes participated in incubation. Nesting success and hatching success were 91% and 58% respectively. Parental care was well marked. Scarcity of nesting sites especially due to modern use of timber and iron, the matchbox style of houses and lack of invertebrate food, change in life style and competition from mynah were found to be the problems house sparrows face in breeding.